Implementation of motivational interviewing in a fall prevention exercise program: experiences from a randomized controlled trial - Marina Arkkukangas (BMC Research Notes, 2019)
Abstract Objective The elderly population over 65 is increasing globally, and interventions promoting health and preventive work, especially fall prevention, will constitute a large part of physiotherapists’ duties in the near future. To address the challenges of promoting effective and sustainable health behavior changes among older persons, physiotherapists need support when it comes to how to apply behavior change strategies, especially in fall prevention. Therefore, the aim of this study was to describe implementation of motivational interviewing in a fall prevention exercise program. This study is a side product of another project. Results Data from a recently performed three-armed randomized controlled trial were used to describe the implementation of motivational interviewing in the exercise group (n = 58). Level of motivation (priorities) and self-efficacy for both the physiotherapist and the participant in treatment, and to use a guide targeted towards the planned treatment are recommended actions. Regular meetings and follow ups as well as updates of motivational interviewing skills during a treatment period, should also be considered to achieve treatment fidelity. Trial registration NCT01778972, Retrospectively registered January 29, 2013